2014
DOI: 10.1523/jneurosci.3066-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ectopic Colonies That Form in Widespread Areas of the Nervous System with Neural Stem Cell Transplants into the Site of a Severe Spinal Cord Injury

Abstract: We reported previously the formation of ectopic colonies in widespread areas of the nervous system after transplantation of fetal neural stem cells (NSCs) into spinal cord transection sites. Here, we characterize the incidence, distribution, and cellular composition of the colonies. NSCs harvested from E14 spinal cords from rats that express GFP were treated with a growth factor cocktail and grafted into the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Ectopic cell collections were rare. It has been reported that grafts of NSCs can form ectopic cell deposits remote from the site of grafting (45,46). In this experiment, remote cell deposits occurred in 2 of 18 animals (11%) (Supplemental Figure 9, C-F), and local extra-pial cell spreading was confined to 1 to 2 spinal segments from the graft site in 5 of 18 animals (28%).…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Ectopic cell collections were rare. It has been reported that grafts of NSCs can form ectopic cell deposits remote from the site of grafting (45,46). In this experiment, remote cell deposits occurred in 2 of 18 animals (11%) (Supplemental Figure 9, C-F), and local extra-pial cell spreading was confined to 1 to 2 spinal segments from the graft site in 5 of 18 animals (28%).…”
Section: Resultssupporting
confidence: 49%
“…Previously, Goldman and colleagues reported long-term safety and efficacy after administration of human glial progenitor cells in rodent demyelinating disease models (15), and Zhang and colleagues reported the functional integration of human-derived astrocytes into intact rodent spinal cord, including investment of astrocytic processes around host neurons and extension of end feet around blood vessels (44). Similarly, ectopic clusters of cells that have been previously reported (45,46) with our grafting technique were only rarely observed at prolonged time points (2 of 12 animals surviving 6 months or longer) and did not compress jci. The NSC graft area was measured using ImageJ software (NIH) on images of fixed box size at 1,600 × 1,200 pixels and ×20 magnification, using every sixth horizontal section that contained GFPexpressing graft.…”
Section: Discussionmentioning
confidence: 79%
“…A recent study from the Steward lab reported that transplantation of a mixed population of glial and neuronal progenitors into a transection model of SCI resulted in ectopic engraftment of large numbers of graft-derived cells in locations such as the central canal, ventricles and pial surface of the spinal cord (Steward et al, 2014), providing a note of caution when using transplantation of any class of NSC/NPC in SCI. This issue is particularly relevant to strategies employing cells derived from pluripotent sources such as ES and iPS cells given the possibility of incomplete and/or inefficient differentiation (Tsuji et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The replication study clarified some methodological issues regarding transplantation techniques and demonstrated the need for follow-up studies to improve formation of continuous tissue bridges between rostral and caudal segments. Interestingly, during the replication study, we also discovered ectopic colonies of graft-derived cells at long distances from the transplant in the central canal, 4 th ventricle and the subdural surface of the spinal cord and brain stem (Steward et al, 2014a; Steward et al, 2014b). It remains to be seen whether these colonies reflect the unique conditions of the experiment, for example the treatment of cells with growth factor cocktail, or whether fetal cells that are still capable of self-renewal (i.e.…”
Section: Introductionmentioning
confidence: 96%